2011
DOI: 10.1519/jsc.0b013e3181fef720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 6-Week Plyometric Training Program on Performances in Pubescent Swimmers

Abstract: This study examined in pubescent swimmers the effects on front crawl performances of a 6-week plyometric training (PT) in addition to the habitual swimming program. Swimmers were assigned to a control group (n = 11, age: 14.1 ± 0.2 years; G(CONT)) and a combined swimming and plyometric group (n = 12, age: 14.3 ± 0.2 years; GSP), both groups swimming 5.5 h · wk(-1) during a 6-week preseason training block. In the GSP, PT consisted of long, lateral high and depth jumps before swimming training 2 times per week. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 15 publications
3
74
0
1
Order By: Relevance
“…As it is well accepted that jump performance can be used a predictor of muscular power [29], the significant increase in jump height (p < 0.05; ES = -1.26), as measured by the CMJ, suggests that over the 7-week period, swimmers significantly increased their lower body power. Similarly, the mean coefficient of variation for the leg dynamometer test has been reported to be 9% in adolescent boys [21] therefore, the significant increase of 28% in leg and back strength (p < 0.05; ES = -1.85) suggests that there was a meaningful increase in lower body strength.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As it is well accepted that jump performance can be used a predictor of muscular power [29], the significant increase in jump height (p < 0.05; ES = -1.26), as measured by the CMJ, suggests that over the 7-week period, swimmers significantly increased their lower body power. Similarly, the mean coefficient of variation for the leg dynamometer test has been reported to be 9% in adolescent boys [21] therefore, the significant increase of 28% in leg and back strength (p < 0.05; ES = -1.85) suggests that there was a meaningful increase in lower body strength.…”
Section: Discussionmentioning
confidence: 97%
“…Due to lack of experience with strength and power training and the age of the swimmers within this study the increase in strength and power is likely to be largely due to neural factors such as increased Motor Unit (MU) activation and improvement in MU coordination, recruitment and firing [29]. Although this is somewhat speculative, the decrease in fat free mass (kg) and muscle mass (kg) in the male participants (p < 0.05) and lack of changes in the female participants (p > 0.05) over the 7 weeks suggests that muscle hypertrophy was not a significant factor in the increase in strength and power and that the improvements were in fact primarily due to improvements in neuromuscular efficiency [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported a significant difference (p<0,05 of relationship was found in the present study, which means that the findings of the present research are in agreement with the study conducted by Özüak (1996). Potdevin et al (2011), who studied the effects of plyometric trainings on land with body weight 2 days a week for 6 weeks among 23 female and male participants of age average 14,1±0,2, reported that the trainings had a positive effect on the performance of their participants. They found significant differences in 50 metre and 400 metre performances of their participants (p<0,05).…”
Section: Discussionmentioning
confidence: 99%
“…The current body of research has focused on the turns in swimming performances, primarily in the front crawl Blanksby, Gathercole, & Marshall, 1996;Lyttle, Blanksby, Elliott, & Lloyd, 1999;Lyttle & Mason, 1997;Pereira, Araújo, Freitas, Gatti, & Silveira 2006;Potdevin, Albety, Chevutschi, Pelayo, & Sidney, 2011;Prins, & Patz, 2006;Silveira et al, 2011). However, research has also been conducted in the turns of other movement patterns, including the backstroke, butterfly, and breaststroke (Blanksby, Skender, Elliott, McElroy, & Landers, 2004;TournyChollet, Chollet, Hogie, & Papparodopoulos, 2002).…”
mentioning
confidence: 99%